Output voltage control of a PMSG with the DPC-SVM technique and high-order sliding mode - Mohammed Moumna; Rachid Taleb; Zinelaabidine Boudjema (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This paper aims to study the control of the output voltage of a wind turbine (WT) which is composed of a permanent magnet synchronous generator (PMSG) connected to an inverter/rectifier. The first tested control on PMSG is based on the classical direct power control (CDPC); this technique uses the active and reactive power as a control variable. Then, to improve the quality of energy and evaluate the performance of the system, we proposed a high-order sliding mode (HOSM) with space vector modulation (SVM) to controlthe output voltage. As a result, the proposed approach presents attractive features such as the chattering-free behavior of the sliding mode. This system was designed for a wind power conversion application in the case of an isolated site. The computer simulations were provided to verify the validity of the proposed control algorithm using the MATLAB/Simulink software.